FAKTOR YANG MEMPENGARUHI MAHASISWA MEMILIH PROGRAM STUDI PENDIDIKAN LUAR SEKOLAH DI UNIVERSITAS RIAU - ', Aymelini; Bahar, Aswandi; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is based on the increasing number of students who continue their study in Out of School Education Study Program, University of Riau. The research problem is whether the factor that influences student choose out of school education in University of Riau?. The purpose of this study was to determine the factors that affect students choose Out of School Education Study Program in University of Riau. The population in this research as many as 181 students of Out of School Education in University of Riau and the sample of this research is 64 students of Out of School Education in University of Riau with a crisis level of 10%, the sample used is proportionate stratified random sampling. The data collection instrument is a questionnaire with 52 statements and after the trial, there are 46 valid statements to be used as research instruments. Data analysis through Quantitative Descriptive analysis. From the calculation of percentage of answers obtained the findings of research Factors Affecting Students Choosing Out of School Education Study Program in University of Riau is an internal factor with the percentage value (SS + S) 70.93% This means that internal factors have a high influence on students in choosing Out of School Education Study Program in University of Riau.Keywords: Factor Affecting, Out of School Education Study Program